Diagnosing pathologic complete response in the breast after neoadjuvant systemic treatment of breast cancer patients by minimal invasive biopsy: oral presentation at the San Antonio Breast Cancer Symposium on Friday, December 13, 2019, Program Number GS5-03 - Heil, Jörg; Pfob, André; Sinn, Peter; Rauch, Geraldine; Bach, Paul; Thomas, Bettina C.; Schäfgen, Benedikt; Kuemmel, Sherko; Reimer, Toralf; Hahn, Markus; Thill, Marc; Blohmer, Jens-Uwe; et al. (Annals of surgery, 2022)
We evaluated the ability of minimally invasive, image-guided vacuum-assisted biopsy (VAB) to reliably diagnose a pathologic complete response in the breast (pCR-B). Neoadjuvant systemic treatment (NST) elicits a pathologic complete response in up to 80% of women with breast cancer. In such cases, breast surgery, the gold standard for confirming pCR-B, may be considered overtreatment.
Originally published: July 09, 2020
Gesehen am 24.02.2022